Tinjauan Kriminologis Terhadap Kejahatan Klitih yang Dilakukan Oleh Siswa Sekolah Menengah Atas di Bantul - Dinda Anissa Ramadani; Ariesta Wibisono Anditya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2025)
Klitih is a juvenile delinquency which is quite concerning because the case occurs every year in Yogyakarta and one of them is in Bantul Regency. Klitih basically not a new crime but old one. Klitih violence can harm individuals and lead to disorder and turmoil in the surrounding community. Klitih has the meaning of an activity of someone who leaves the house at night with no particular purpose or is the same as wandering around. In criminology, klitih is a subcultural deviation that determines how crime becomes a culture or crime as a culture in social terms. This study used the field research method and the library research method which was carried out at the Bantul Police office by taking data files to find out the number of cases and data on the age of the perpetrators as well as interviews. The results obtained by researchers in this study include. (1) Factors causing the crime of klitih in Bantul Regency include: Family factors, hurt or resentment factors and environmental factors. (2) Counseling teacher's efforts to deal with students who commit crimes and violence in the school environment.